FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN LEMBAGA PERKREDITAN DESA DI DESA ADAT MENGWITANI KECAMATAN MENGWI KABUPATEN BADUNG - I MADE HARY KUSMAWAN; I WAYAN SUARBAWA; I KADEK YOGI RIANA (GANEC SWARA, 2022)
Village Credit Institutions (LPD) of Mengwitani Village has a major contribution in driving the community’s economy of Mengwitani Village. Because of its big role, then LPD of Mengwitani Village have to continue to be develop especially, to achieve income. Furthermore, the aim of this study is to find out the effect of capital, non-performing loans and savings partially or simultaneously on the income of LPD of Mengwitani Village. The data analysis was done by multiple linear regression method. Based on the result of SPSS data analysis obtained that capital was not significantly affect partially on the income of LPD of Mengwitani Village, while non-performing loans and savings significantly affect partially on the income of LPD of Mengwitani Village. From the estimation results of model showed F count value of 600,109 with F table value of 2,82 then F count bigger than F table (600,109 > 2,82). The significance value was 0,000 smaller than probability value 0,05 (0,000 < 0,05) then Ho rejected and Ha accepted, means the independent variables which was capital, non-performing loans and savings significantly affect on dependent variable which was the income of LPD of Mengwitani Village. R square equal to 0,976 which means capital, non- performing loans and savings simultaneously gave contribution or effect of 97,6%, on the income of LPD of Mengwitani Village, while the rest of 2,4% affected by other variables which was not mentioned in this study